Antigen-Sparing and Enhanced Efficacy of Multivalent Vaccines Adjuvanted with Immunopotentiators in Chickens - Wu, Peipei; Lu, Jihu; Feng, Lei; Wu, Hongzhuan; Zhang, Xuehua; Mei, Mei; Hou, Jibo; Liu, Xiufan; Tang, Yinghua (Frontiers in Microbiology, 2017)
We previously described that immunopotentiators, CVCVA5, increased the efficacy of H5 and H9 subtype avian influenza vaccines in chickens, ducks and geese. In this study, we further investigated the effects of the CVCVA5 for improving the efficacy of other univalent or multivalent inactivated vaccines. The immune response administrated with half-dose of monovalent vaccine plus CVCVA5 were higher than those of one dose of monovalent vaccine without immunopotentiators as measured by levels of antibodies from serum, tears and bronchoalveolar lavage fluids, and cytokines of IFNγ and IL-4 from serum. Vaccines included the univalent vaccine of Newcastle Disease virus (ND), Egg Drop Syndrome virus (EDS), Infectious Bronchitis virus (IB) and Infectious Bursal Disease virus (IBD). The CVCVA5 also improved the immune response of both ND and IBD vaccines with less dosage. The sterile protective immunity was monitored with one- or a half-dose of adjuvanted ND vaccine or one dose of adjuvanted IBD vaccine, respectively. The improved immune efficacy was observed in a half-dose of adjuvanted bivalent vaccines compared to one dose of vaccines without CVCVA5 as measured by the antibody levels, including bivalent vaccine of ND-H9, ND-IB and ND-IBD. The CVCVA5 also boosted the immune efficacy of the tetravalent vaccine (ND-IB-EDS-H9). A half-dose of adjuvanted commercial vaccine or 75% antigen-sparing adjuvanted vaccine elicited similar antibody levels to those of one dose non-adjuvanted commercial vaccines . The CVCVA5 improved the effect of a booster vaccination as measured by the antibody levels against H5 or H9 virus antigens, in which chickens primed with the adjuvanted ND-IB vaccines given a booster with H5-H9 bivalent vaccines without CVCVA5 using 5-day intervals. The inflammatory response may contribute to these additional effects by increasing the levels of IFNγ and IL-4 after the injection of the adjuvanted ND-IB vaccines. Results indicated that the CVCVA5 improved the serum and mucosal antibody levels, cytokine levels of the chickens given the univalent vaccine, and also improved serum antibody titers in bivalent and tetravalent vaccines . This has a potential as an improve vaccine.